IS RUSSIA A THREAT TO ESTONIAN ENERGY SECURITY? - and Matthew Crandall, Triinu Tarus (Baltic Journal of Political Science, 2012)
This study examines whether Russia is a threat to Estonia’s energy security as well as how Estonia has reacted to Russia as an energy supplier. The authors use Stephen Walt’s balance of threat theory as a framework to understand the potential of Russia as a threat, as well as how Estonia has reacted. The balance of threat theory is chosen because it effectively establishes when states view others as a threat and how they react. The focus of the work is on Estonia’s dependence on Russian natural gas and the great lengths Estonia has gone to be energy self-sufficient. The article concludes that Estonia can and does see Russia as a threat to its energy security and has taken significant measures to reduce its dependency on Russia as an energy supplier.